2020
DOI: 10.1080/14735903.2020.1743553
|View full text |Cite
|
Sign up to set email alerts
|

Using co-constructed mental models to understand stakeholder perspectives on agro-ecology

Abstract: Agro-ecology has been recognized as a potential route to realizing the multiple economic, social, and environmental benefits increasingly required of agricultural systems. However, views on what constitutes agro-ecology differ considerably between countries, and also between stakeholder groups such as natural scientists and farmers. To identify areas of convergence and divergence in understandings of agro-ecology in the Scottish context, we used a novel co-constructed mental modelling approach with a sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 32 publications
(32 reference statements)
0
22
0
Order By: Relevance
“…Some articles have addressed environmentally friendly agricultural systems such as organic farming [190][191][192][193][194] and agro-ecology [190,195,196], biodynamic agriculture [197,198], and conservation agriculture [199]. Migliorini and Wezel [190] suggested that "Both agroecology and organic agriculture offer promising contributions for the future development of sustainable agricultural production and food systems, especially if their principles and practices converge to a transformative approach and that impedes the conventionalisation of agrofood systems".…”
Section: Bibliographical Analysismentioning
confidence: 99%
“…Some articles have addressed environmentally friendly agricultural systems such as organic farming [190][191][192][193][194] and agro-ecology [190,195,196], biodynamic agriculture [197,198], and conservation agriculture [199]. Migliorini and Wezel [190] suggested that "Both agroecology and organic agriculture offer promising contributions for the future development of sustainable agricultural production and food systems, especially if their principles and practices converge to a transformative approach and that impedes the conventionalisation of agrofood systems".…”
Section: Bibliographical Analysismentioning
confidence: 99%
“…Ambiguity round the concept of agroecology is not typically Dutch (see, e.g. van Hulst et al, 2020). With a concrete measure such as herb-rich grasslands it may be possible to realize synergies.…”
Section: Condition 1: Concrete Goals or Actionsmentioning
confidence: 99%
“…However, what they all have in common is that they are models of people's mental structures that have been translated into conceptual interlinked systems. Thus, the use of mental models techniques facilitates system thinking, sheds light on different perspectives on an issue, offers the possibility to derive suitable solutions, and supports decision-making for innovation processes by revealing the shared and complementary views of the actors (Biggs et al 2011;Prager and Curfs 2016;van Hulst et al 2020). Applying a qualitative mental model technique can reveal deep insights into the thinking of people and allow for comparisons of their individual patterns by displaying overlaps and divergences (van Hulst et al 2020).…”
Section: Data Analysis Procedures (Semantic Web Analysis)mentioning
confidence: 99%